1999
DOI: 10.2307/1549254
|View full text |Cite
|
Sign up to set email alerts
|

Feeding, Respiration, and Aerial Exposure in a Scavenging Cirolanid Isopod From New Zealand

Abstract: The feeding rate, oxygen consumption, and effects of aerial exposure were measured for a cirolanid isopod, Natatolana rossi, collected from a shallow subtidal habitat at Kaikoura, New Zealand. The isopod survived 7 days exposure in water-saturated air at 15°C and mean survival time was similar both in water-saturated air (5.1 days) and water (4.6 days) at 1°C.Weight loss in aerial conditions increased both with time and with decreasing relative humidity (RH). Weight-specific transpiration rates (mg water los… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…This strategy, and scavenging, as seen in Cirolanidae, would seem to be the plesiomorphic strategy within this clade. Some species of Natatolana are scavengers and will enter baited traps (Arntz and Gutt 1999;Marsden 1999;Storch et al 2002). Cirolanid diversity is higher in tropical than cooler regions (Bruce 1986;Keable 1995) and correlates with a more diverse food supply, exemplified by the diversity of a typical food source: fishes.…”
Section: Radiation Ecology and Biogeographymentioning
confidence: 99%
“…This strategy, and scavenging, as seen in Cirolanidae, would seem to be the plesiomorphic strategy within this clade. Some species of Natatolana are scavengers and will enter baited traps (Arntz and Gutt 1999;Marsden 1999;Storch et al 2002). Cirolanid diversity is higher in tropical than cooler regions (Bruce 1986;Keable 1995) and correlates with a more diverse food supply, exemplified by the diversity of a typical food source: fishes.…”
Section: Radiation Ecology and Biogeographymentioning
confidence: 99%
“…Nilsson et al (2004) found the coral dwelling goby Gobiodon histrio able to withstand 3 h of air exposure. Marsden (1999) demonstrated that the cirolanid isopod, Natatolana rossi, is capable of extended periods of aerial exposure and suggested that this adaptation is a possible response to inadvertent displacement into intertidal habitats. An examination of either their relative ability to find water of better quality or amphibious activity may be informative, as it seems that thermal tolerance alone is insufficient to explain the vertical zonation patterns exhibited by these intertidal fishes.…”
Section: Behavioural Responses To Temperaturementioning
confidence: 99%
“…Isopods of the family Cirolanidae are distributed worldwide, including marine, estuarine and some freshwater environments (Bruce et al, 2002). Some cirolanids are micro-predators on the surface of fishes or invertebrates (Bruce, 1986;Brusca et al, 1995), other species are scavengers on marine fauna with no apparent preference for particular carrion types (Stepien & Brusca, 1985;Bruce, 1986;Berrow, 1994;Keable, 1995;Wong & Moore, 1995, Marsden, 1999. For some species it is not clear if they are only scavengers or also predators (Bunkley- Williams & Williams, 1998).…”
Section: Introductionmentioning
confidence: 99%